Antibacterial mechanism of Tetrapleura tetraptera extract against Escherichia coli and Staphylococcus aureus and its application in pork. Issue 6 (30th August 2019) - Lin, Lin; Agyemang, Kwabena; Abdel‐Samie, Mohamed Abdel‐Shafi; Cui, Haiying
Abstract: The antibacterial activity and the mechanism of Tetrapleura tetraptera root extract against Escherichia coli and Staphylococcus aureus were investigated. The mechanism of action of T. tetraptera on tested bacterial species was predominantly characterized by the study of transmission electron microscopy, which revealed severe damage on the primary target which affected the cell integrity and cell membrane permeability. The loss of soluble proteins studied by bacterial protein sodium dodecyl sulfate–polyacrylamide gel electrophoresis analysis and the decreased adenosine triphosphate and DNA contents confirmed the leakage of cell wall. In addition, the studies revealed that the root extract of T. tetraptera could also disrupt the respiratory metabolism by inhibiting the bacteria through the Embden–Meyerhof–Parnas and the hexose monophosphate pathways. T. tetraptera extract possessed a high level of antimicrobial activity in pork, which significantly reduced total viable bacterial population. This study clearly indicates that the T. tetraptera could be a potential source of new antimicrobial agent which has proven effective activity against antibiotic‐resistant strains of pathogens. Practical Applications: Tetrapleura tetraptera is a flowering plant native to Africa with a wide range of applicability in local cuisines and traditional medicine. The T. tetraptera root extract possesses high antimicrobial activity against both gram‐positive and gram‐negative bacteria. This study could contribute to the better understanding of antibacterial mechanism of T. tetraptera . As a natural food preservative, it has broad prospect to be utilized in the meat industry.